Modelling drivers of Brazilian agricultural change in a telecoupled world. (May 2021) - Millington, James D.A.; Katerinchuk, Valeri; Silva, Ramon Felipe Bicudo da; Victoria, Daniel de Castro; Batistella, Mateus
Abstract: Increasing global demand for agricultural commodities has driven local land use/cover change (LUCC) and agricultural production across Brazil during the 21st century. Modelling tools are needed to help understand the range of possible outcomes due to these 'telecoupled' global-to-local relationships, given future political, economic and environmental uncertainties. Here, we present CRAFTY-Brazil, a LUCC model representing production of multiple agricultural commodities that accounts for spatially explicit (e.g., land access) and temporally contingent (e.g., agricultural debt) processes of importance across our nearly four million km 2 Brazilian study area. We calibrate the model calibration for 2001–2018, and run tests and scenarios about commodity demand, agricultural yields, climate change, and policy decisions for 2019–2035. Results indicate greater confidence in modelled time-series than spatial allocation. We discuss how our approach might be best understood to be agency -based, rather than agent-based, and highlight questions more and less appropriate for this approach. Highlights: We develop and use a simulation model to examine telecoupled agricultural change. The CRAFTY-Brazil model simulates land use/cover change and agricultural production. For 10 Brazilian states we calibrate for 2001–18, running tests/scenarios for 2019–35. Results indicate greater confidence in modelled time-series than spatial allocation. We discuss how our approach is agency-based, not agent-based, and what this implied.